EFL Students’ Mastery of English Grammar across Proficiency Levels - Riki Muhamanda; Faisal Mustafa (Proceedings of AICS - Social Sciences, 2017)
TOEFL is usually used as a placement test to categorize students into different class levels in English language training. All levels are usually taught similar materials with different complexity levels. However, TOEFL result can be used to decide what materials can be skipped for a certain level of students, especially for advanced level. The aim of this research was to find out level of student mastery of grammar based on their level of English. For this purpose, TOEFL test was given to 299 students at Syiah Kuala University at different occasions. The test results were analyzed by calculating percentages of correct answers for each grammatical item tested in the TOEFL. The percentages were observed separately for each proficiency level to determine the grammatical items that students with each level of English have mastered. The results showed that students have mastered concepts related to word order, passive voice, and word form when their structure score in the TOEFL reach 450, comparison when 480, and reduced adjective clause when 510. Therefore, when students reach certain level of English based on their TOEFL score, grammatical items related to word order, passive voice, word form, comparison, and reduced adjective clause can be skipped in the teaching and learning process. Keywords:placement test, TOEFL, grammar mastery, EFL learners.